The complicated relationship between climate, conflict, and gender in Mozambique - Maviza, Gracsious; Mandlenkosi, Maphosa; Caroli, Giulia; Synnestvedt, Thea; Tarusarira, Joram (2024)
Individuals face immense challenges in displacement contexts, particularly where climate, conflict, and displacement intersect. In Mozambique, climate impacts have combined with conflict to displace nearly a million people. Entire livelihoods, identities, and stability are vanishing. Women, men, girls, and boys are not just losing homes; they are losing their place in traditional societal roles, too. This chaos—and responses by the international community—are reshaping Mozambique’s gender dynamics.